PENINGKATAN HASIL BELAJAR SISWA PADA MATERI BARISAN DAN DERET ARITMATIKA DENGAN MENGGUNAKAN MODEL DISCOVERY LEARNING - Salsabila Fitria Khoerunnisa; Eka Senjayawati; Gida Kadarisma (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
The research was conducted to improve student learning outcomes on Arithmetic Rows and Series materials by applying the discovery learning model, based on of student learning outcomes being still low and difficulties in understanding and remembering the concepts of Arithmetic Rows and Series materials. The type of research used is classroom action research (CAR) which lasts for 2 cycles. The subjects of this research were 26 students of class X from one of the Vocational Schools in Cimahi. Data collection techniques in the form of observations, interviews and test questions. The data obtained are then analyzed qualitatively. The results showed that the percentage of student learning outcomes with scores above 70 before being given action or pre-cycle was 0.00% then after being given action the percentage continued to increase in each cycle. The percentage in the first cycle was 7.69% and in the second cycle was 96.15%. All data results in this study were processed using Microsoft Excel by looking for the percentage of the average value in each cycle. Based on the results of the research, it can be seen that the use of the discovery learning model can improve the learning outcomes of Vocational  School students on arithmetic sequences and series.